A COMPARATIVE SURVEY ON WIRELESS INTERNET USAGE AND FUTURE EXPECTATIONS OF UNIVERSITY STUDENTS (THE CASES OF USF, AKU AND IUS). - Koçak, Hüseyin; Dündar, Süleyman; Arslan, Hüseyin (Epiphany, 2015)
This article addresses the question of college students' internet usage and their expectations for better wireless access. Wireless and mobile internet access recently became an integral part of our lives. Especially given the introduction of smart devices (phones, tablets etc.) into the wireless market and the vast number of applications running on these devices, it is possible to become addicted to these devices. Some of us have come to a point where we can leave everything behind us except our phones. To better understand how wireless access has influenced us we conducted a face-toface survey with three different groups of college students totalling 829. According to the survey, there are some problems while using the internet, such as internet speed and connection. University students do not want to give up mobile communications and they never want to be secondary users. They pay more attention to security and privacy in communication. They are also awaiting functional innovations in future.